Practical approach to the diagnosis and therapy of hyponatremia - Zoltán Nádházi (Cardiologia Hungarica)
Hyponatremia is one of the most common electrolyte abnormalities in clinical practise. Depending on its severity, the clinical presence varies from asymptomatic to life-threatening. Since sodium plays a decisive role in the formation of the body's fluid spaces and the osmotic activity of the blood, clarifying and correcting the etiology of the hyponatremia causing the symptoms is an inevitable task. Mapping the origin of the disease partly determines the therapeutic interventions, and partly it can shed light on the existence of other diseases that may affect life expectancy. In order to clearly determine the underlying disease(s), knowledge of additional characteristics besides hyponatremia (volume status, osmolality conditions, urinary sodium excretion) is often essential. The learned parameters then help to plan further diagnostic steps (e.g. tumor research). After all this, the necessary therapeutic steps are determined by the combination of the detected etiological factor and the clinical presence.